Evolução Cromossômica em Ctenoluciidae (Characiformes) com enfoque na diferenciação de cromossomos sexuais - Sousa e Souza, José Francisco de (Genética, Conservação e Biologia Evolutiva - GCBEv, 2023)
Ctenoluciidae is a freshwater fish family, which currently comprises two genera: Ctenolucius with two species (C. beani and C. hujeta) and Boulengerella with five species (B. cuvieri, B. lateristriga, B. lucius, B. maculata and B. xyrekes), widely distributed in South America. Despite being a small diverse group, cytogenetic data are scarce, and suggest conservation of the diploid number (2n), with 2n=36 chromosomes, evidenced in five of the seven species of this family. However, this conservatism refers only to 2n, since differences in the distribution of some classes of repetitive sequences were resolving markers, to show differential processes of chromosomal evolution between Boulengerella species. Notably, a chromosomal heteromorphism related to the nucleolar pair, associated with an unusual accumulation of telomere sequences, suggested a possible sex chromosome system of the XX/XY type in the analyzed Boulengerella species. However, the CGH analysis did not show sex-specific sequences, leading us to propose that the heteromorphism, evidenced in the nucleolar pair (in males) of Boulengerella species, resulted from the differential expression of 18S rDNA, influenced by the accumulation of different SSR in this region. This study brings evidence of the karyotypic evolution of the Ctenoluciidae family, based on the cytogenomic characterization of Ctenolucius hujeta and four Boulengerella species (named B. cuvieri, B. lateristriga, B. lucius and B. maculata), aiming to understand their genomic organization and mechanisms of chromosomal evolution. For this, conventional cytogenetic data and repetitive DNA mapping (5S and 18S rDNAs, Rex1, Rex3 and Rex6 and microsatellite sequences), Whole Chromosome Painting (WCP) and Comparative Genomic Hybridization (CGH) are presented. The results highlighted that the conservatism in the (2n) evidenced among Boulengerella spp. extends to C. hujeta and is limited to 2n only, with both macro and microstructural differences between species The association of repetitive DNAs and Rex retroelements to 18S and 5S rDNAs played an important role in the formation of chromosomal hotspots that influenced the chromosomal rearrangements evidenced in this family.
Keywords: CITOGENÉTICA; BIOLOGIA MOLECULAR